Developing a governance model for PPP infrastructure service delivery based on lessons from Eastern Australia - Raymond E. Levitt; Kent Eriksson (Journal of Organization Design, 2016)
Public-private partnership (PPP) concession agreements are awarded by National, State and local public agencies that contract with private companies to finance and deliver infrastructure as a long term service to governments and their citizens, rather than having the private firms design and build infrastructure assets to be financed, operated-and, hopefully, maintained-by government. PPPs are similar to the emerging model of selling business or personal software as a cloud-based service (SaaS) rather than as a product licensed by the user-a model that that has transformed and disrupted the enterprise software industry. Australia is a world leader in PPP infrastructure delivery, and has had over two decades of experience in delivering civil and social infrastructure services to its citizens via PPP concessions. Along the way, the public and private participants in infrastructure PPPs have developed practices and a mature institutional framework necessary for this kind of long-term, risky public-private commercial partnership. This study reports the findings from in-depth interviews with 25 senior executives of public and private participants in PPP infrastructure projects from the three Eastern Australian States with the longest history of PPP delivery. Based on the results of those interviews, we develop a governance model for infrastructure service delivery: the government selects infrastructure projects, guided by a non-partisan, expert infrastructure prioritization panel, and contracts for the delivery of these prioritized infrastructure services with a private concessionaire financed by long-term institutional investment capital. The concessionaire is a private entity in charge of financing, designing, constructing, operating, and maintaining the infrastructure service. The government supervises the infrastructure service, to safeguard public interest. The government also provides an institutional framework, with contracts and authorities necessary for the interaction between the public and private actors.
Keywords: 650; Alignment of interest; Conflict of interest; Governance; Infrastructure; Institutional investor; Investment bank; Public-private partnership; PPP; P3; Pension fund; Pension fund aggregator; Infrastructure developer; Structured finance; Relational contracting; risk allocation